Sexual violence as a sexual script in mainstream online pornography - Vera-Gray, F. (The British journal of criminology, 2021)
This article examines the ways in which mainstream pornography positions sexual violence as a normative sexual script by analysing the video titles found on the landing pages of the three most popular pornography websites in the United Kingdom. The study draws on the largest research sample of online pornographic content to date and is unique in its focus on the content immediately advertised to a new user. We found that one in eight titles shown to first-time users on the first page of mainstream porn sites describe sexual activity that constitutes sexual violence. Our findings raise serious questions about the extent of criminal material easily and freely available on mainstream pornography websites and the efficacy of current regulatory mechanisms.